POLA KONSUMSI DALAM ISLAM DAN KONSEP ECO-SUFISME MUHAMMAD ZUHRI - Suwito Suwito (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2011)
This article explores a new view of the relationship between theconsumption patterns and spiritual transformation, which is discussed ina Sufi perspective. Hunger tradition as Sufi’s consumption pattern is seenby Muhammad Zuhri as a medium for self-recognition. If someone hasbeen able to get to know himself, then it will gradually know the qualityof himself. Humans, is individually a weak creature, can not live withoutthe help of another man and the universe. In this context, the cosmos andthe self is